MULTILAYER TREATMENT OF THE NASOGENIAN FROOD - Fernandes Dos Santos Lima, Janaína; Regina Veronezi, Lauscea; Vivianne Nogueira, Marcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
Aging is a physiological process determined by various intrinsic and extrinsic factors, being a normal and inevitable process. A common complaint of the aging process is the crease of the nasolabial folds, popularly known as the “Chinese mustache”. With aging, the progressive ptosis of the malar fat and the overlying skin contribute to the deepening of the sulcus, but the depth also varies according to race, gender, age and weight. Since 1996, HA has been used by dermatologists and plastic surgeons for cosmetic purposes to fill in wrinkles, scars, increase lip volume and others. Although the duration of effect is limited, HA products are the most commonly used fillers. They produce very significant results and few undesirable reactions. Non-surgical procedures with the use of HA for correction of the SNG in the facial rejuvenation process are a reality, and the objective of the present study is to evaluate the effectiveness of the filler based on hyaluronic acid in the nasolabial folds through injection techniques in three dermal planes distinct: supraperiosteal, subcutaneous and intradermal, showing the results.